Влияние способа приготовления среднетемпературного катализатора конверсии оксида углерода водяным паром на его физико-химические свойства - Гармаш, Б. К.; Ворожбиян, М. И.; Лобойко, Алексей Яковлевич; Микиша, Галина Владимировна (НТУ "ХПИ", 2006)
В статті розглянуто вплив засобів приготування середньотемпературного каталізатору конверсії оксиду вуглецю водяною парою на його фізико-хімічні властивості. Наведені данні дослідження пористих характеристик каталізатора. Визначена активність дослідних зразків каталізатора виготовлених різними засобами.

In the article the influence of ways of preparation of high-temperature catalyst of carbon monoxide conversion with water gas on physical and chemical properties of this catalyst is studied. Data of the investigations of pore characteristics of the catalyst are given. The activity of tested samples of the catalyst prepared by means of various ways is determined.
Keywords: семиводный железный купорос; оксид железа; титановые белила; осаждение; щелочной металл; порометрический метод